Phenotypic and Molecular Genetic Variation in Tunisian Natural Populations of Sulla carnosa. (1st July 2013) - Neji, Mohamed; Taamalli, Wael; Smida, Malek; Abdelly, Chedly; Gandour, Mhemmed
Abstract : Sulla carnosa (Desf.) is a diploid (2 n = 16), allogamous, seed‐propagated species and has a vegetative shoot system characterized by an orthotropic main stem bearing some lateral plageotropic shoots. It is of interest for rangeland revegetation and production. In this study, we analyzed the genetic diversity of five S. carnosa populations using 15 quantitative traits and nine random amplified polymorphic DNA primers. A total of 14 and 41% of the total genetic variation was found among the populations for molecular and phenotypic traits, respectively ( G st = 0.14 and Q st = 0.41). Despite the relatively high level of gene flow among populations ( Nm = 3.1 or 0.065 individuals per generation), results showed a significant isolation by distance. Correlations between characters as well as with climatic region were established. The most significant positive correlations were found between features related to plant strength, while the most significant negative correlations were found between the flowering time and traits related to plant strength. When correlated to climatic region, plant height ( r = –0.75, P = 0.000) and flowering date ( r = –0.71, P = 0.000) showed the most significant estimates, indicating a gradual variation of these phenotypic traits. These results suggest a prominent role for natural selection in accounting for patterns of genetic differentiation of quantitative traits among natural populations of S. carnosa .